Kinerja Bank Perkreditan Rakyat di Kabupaten Badung Bali Sebelum dan Selama Pandemi Covid-19 - I Wayan Budi Satriya; Ni Komang Sumadi; Sang Ayu Putu Arie Indraswarawati (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The financial performance of the banking sector is very important because it can be an early indication of a financial crisis, which can trigger an economic crisis in a country. The purpose of this study was to determine the financial performance of Rural Banks (BPR) in Badung Regency, Bali Province before and during the covid-19 pandemic. BPR financial ratio data for the 2016-2019 period is used as BPR performance data before the covid-19 pandemic, while financial ratios in 2020 are used as BPR performance data during the covid-19 pandemic. The results showed that the CAR ratio increased and differed significantly compared to before the covid-19 pandemic. The NPL ratio also shows an increase and is significantly different compared to before the covid-19 pandemic. The ROA ratio shows a decrease and is significantly different compared to before the covid-19 pandemic. The BOPO ratio shows an increase and is significantly different compared to before the covid-19 pandemic. Meanwhile, the LDR ratio showed an increase but was not significantly different from before the covid-19 pandemic. The change in financial ratios shows a decline in the performance of BPRs in Badung Regency during the covid-19 pandemic.